Wear behaviour of a Cu-Ni-Sn hybrid composite reinforced with B4C prepared by powder metallurgy technique - Allasi, Haiter Lenin (Strojniški vestnik, 2023)
Cu matrix composites benefit from the high electrical and thermal conductivities of Cu and the mechanical wear/erosion resistance of hard reinforcement. In this study, an attempt has been made to determine the effect of the addition of reinforcement B4C in Cu-Ni-Sn. The B4C is reinforced to form a hybrid Cu matrix composite with powder metallurgy technique. The hybrid composites are obtained by milling, blending, and compacting the powders to obtain a fine grain-sized particle without aggregation. The grain size and particle nature were characterized using scanning electron microscope (SEM) and X-ray diffraction (XRD) techniques, respectively. The microstructure, density, hardness, and wear rate of the composites were studied. The pin-on-disc method is equipped to study the wear behaviour and coefficient of friction. The sintered density of the prepared Cu-15%Ni is 98.25 %, Cu-8%Sn is 98.20 %, Cu-15%Ni-8%Sn is 98.10 % and Cu-15%Ni-8%Sn-2%B4C is 95.26 % and lower specific wear rate has been recorded for Cu-15Ni-8Sn-2B4C 121×10-6 mm3/(Nm) and the addition of reinforcement B4C in Cu-Ni-Sn displays remarkable changes in wear rate and friction coefficient.
Keywords: baker; characterization; composites; copper; density; gostota; hibridni kompoziti; karakterizacija; metalurgija prahov; obraba; powder metallurgy; rentgenska difrakcija; vrstični elektronski mikroskop; wear